Implementasi Pembelajaran SKI Berbasis Mind Mapping Kelas X di MAS Sumbersari Kowang Tuban Tahun Pelajaran 2024-2025 - Latif, Isnawati Nur Afifah; Robby, Muhammad Misbahur; Sugondo, Sugondo; Al Ulumi, Abdullah Chabib (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2025)
The learning method is one of the external factors that significantly influences students' motivation and enthusiasm during the learning process. One method considered effective in creating an active and engaging learning atmosphere is the mind mapping method. This technique encourages students to think creatively by organizing information visually and systematically, often through group collaboration involving students with diverse abilities. This study aims to examine the implementation of the mind mapping method in the learning of Islamic Cultural History (SKI) for Grade X students at MAS Sumbersari Kowang, as well as to evaluate the extent to which this method enhances student participation and understanding of the learning material. Most SKI learning sessions have traditionally relied heavily on the lecture method, which tends to be one-way and often causes students to become passive and easily bored. Therefore, applying the mind mapping method is expected to serve as an alternative solution to create a more interactive and enjoyable learning experience. This research adopts a qualitative descriptive approach in the form of classroom action research (CAR) conducted in one cycle. The results indicate that the mind mapping method significantly increases student engagement in learning. Previously passive students began to actively participate during group discussions, the creation of mind maps, and class presentations. Thus, this method can serve as an effective alternative to improve the quality of SKI learning at the senior Islamic high school level.